N-Domain Isoform of Angiotensin I Converting Enzyme as a Marker of Hypertension: Populational Study - Leila C. V. Maluf-Meiken; Fernanda B. Fernandes; Danielle S. Aragão; Fernanda A. Ronchi; Maria C. C. Andrade; Maria C. Franco; Andreia C. S. Febba; Frida L. Plavnik; José E. Krieger; Jose G. Mill; Ricardo C. C. Sesso; Dulce E. Casarini (International Journal of Hypertension)
The aim of this paper was to investigate the presence of the urinary 90 kDa N-domain ACE in a cohort of the population from Vitoria, Brazil, to verify its association with essential hypertension since this isoform could be a possible genetic marker of hypertension. Anthropometric, clinical, and laboratory parameters of the individuals were evaluated (n=1150) and the blood pressure (BP) was measured. The study population was divided according to ACE isoforms in urine as follows: ACE 65/90/190, presence of three ACE isoforms (n=795), ACE 90+ (65/90) (n=186), and ACE 90− (65/190) (n=169) based on the presence (+) or absence (−) of the 90 kDa ACE isoform. The anthropometric parameters, lipid profile, serum levels of uric acid, glucose, and the systolic and diastolic BP were significantly greater in the ACE 90+ compared with the ACE 90− and ACE 65/90/190 individuals. We found that 98% of individuals from the ACE 90+ group and 38% from the ACE 65/90/190 group had hypertension, compared to only 1% hypertensive individuals in the ACE 90− group. There is a high presence of the 90 kDa N-domain ACE isoform (85%) in the studied population. The percentile of normotensive subjects with three isoforms was 62%. Our findings could contribute to the development of new efficient strategy to prevent and treat hypertension to avoid the development of cardiovascular disease.